2012
DOI: 10.1007/s10886-012-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Evolution of Soil Nematode Chemotaxis

Abstract: Plants influence the behavior of and modify community composition of soil-dwelling organisms through the exudation of organic molecules. Given the chemical complexity of the soil matrix, soil-dwelling organisms have evolved the ability to detect and respond to these cues for successful foraging. A key question is how specific these responses are and how they may evolve. Here, we review and discuss the ecology and evolution of chemotaxis of soil nematodes. Soil nematodes are a group of diverse functional and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 99 publications
0
97
0
2
Order By: Relevance
“…La diferencia en la condición R, T y HPS de acuerdo con el número de NF en suelo y raíz tiene su origen en aspectos de la biología de los nematodos (por ejemplo, el ciclo de vida), y la interacción nematodo-arvense (por ejemplo, el tipo de parasitismo). La densidad de NF en suelo está relacionada con la liberación de sustancias químicas (exudados) a través de las raíces, las cuales constituyen atrayentes de NF hacia la planta (Curtis, 2008;Rasmann et al, 2012;Dong et al, 2014). Este fenómeno podría hacer que una arvense adquiera una condición R o T con base en un número alto de NF en suelo.…”
Section: Delilia Bifloraunclassified
“…La diferencia en la condición R, T y HPS de acuerdo con el número de NF en suelo y raíz tiene su origen en aspectos de la biología de los nematodos (por ejemplo, el ciclo de vida), y la interacción nematodo-arvense (por ejemplo, el tipo de parasitismo). La densidad de NF en suelo está relacionada con la liberación de sustancias químicas (exudados) a través de las raíces, las cuales constituyen atrayentes de NF hacia la planta (Curtis, 2008;Rasmann et al, 2012;Dong et al, 2014). Este fenómeno podría hacer que una arvense adquiera una condición R o T con base en un número alto de NF en suelo.…”
Section: Delilia Bifloraunclassified
“…Recent evidence has shown that several species of entomopathogenic nematodes have taken advantage of the volatile compounds emitted by plant roots being attacked by insects to locate the insects, even over long distances. Carbon dioxide (CO 2 ) in the soil indicates a biological activity and has been widely implicated in locating a host (Rasmann et al 2012). Turlings et al (2012) reported that the combination of this gas and specific volatile root compounds is more attractive than when encountered individually, acting synergistically to attract entomopathogenic nematodes.…”
Section: Palavras-chavementioning
confidence: 99%
“…2A). This hatching is induced by some stimuli from the soil or from the root exudates of the plants (Hallem et al, 2011;Rasmann et al, 2012). After penetrating into roots, the J2 larvae migrate intercellularly through cortical cells to search out the vascular cylinder.…”
Section: Establishment Of Syncytia By Cyst Nematodes In Plant Rootsmentioning
confidence: 99%